Child abuse predicts adult PTSD symptoms among individuals diagnosed with intellectual disabilities - Catani, Claudia; Sossalla, Iris M. (Frontiers in Psychology, 2015)
Prior research has shown that people with intellectual disabilities (ID) are more likely to experience child abuse as well as other forms of traumatic events later in life compared to the general population. Little is known however, about the association of these experiences with adult mental health in individuals with ID. The present study aimed to assess whether child abuse in families and institutions as well as other types of adverse life events, were associated with current Posttraumatic Stress Disorder (PTSD) and depression symptoms in individuals with ID. We conducted clinical interviews which included standardized self-report measures for childhood abuse, PTSD, and depression in an unselected sample of 56 persons with a medical diagnosis of intellectual disability who were attending a specialized welfare center. The frequency of traumatic experiences was very high, with physical and emotional child abuse being the most common trauma types. 87% of the persons reported at least one aversive experience on the family violence spectrum, and 50% of the sample reported a violent physical attack later in adulthood. 25% were diagnosed with PTSD and almost 27% had a critical score on the depression scale. Physical and emotional child abuse was positively correlated with the amount of institutional violence and the number of general traumatic events, whereas childhood sexual abuse was related to the experience of intimate partner violence in adult life. A linear regression revealed child abuse in the family to be the only significant independent predictor of PTSD symptom severity. The current findings underscore the central role of child maltreatment in the increased risk of further victimization and in the development of mental health problems in adulthood in individuals with ID. Our data have important clinical implications and demonstrate the need for targeted prevention and intervention programs that are tailored to the specific needs of children and adults with intellectual disabilities.